2022
DOI: 10.3390/tropicalmed7090232
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation and Predictors of Unsuppressed Viral Load among HIV-Positive Men and Women in Rural and Peri-Urban KwaZulu-Natal, South Africa

Abstract: Unsuppressed HIV viral load is an important marker of sustained HIV transmission. We investigated the prevalence, predictors, and high-risk areas of unsuppressed HIV viral load among HIV-positive men and women. Unsuppressed HIV viral load was defined as viral load of ≥400 copies/mL. Data from the HIV Incidence District Surveillance System (HIPSS), a longitudinal study undertaken between June 2014 to June 2016 among men and women aged 15–49 years in rural and peri-urban KwaZulu-Natal, South Africa, were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…The proportion of HIV-positive adolescents on antiretroviral therapy (ART) who were not virologically suppressed after 6 months was 23% in South Africa. WHO stage IV and ART-related facial outcomes were strongly associated with virological non-suppression, whereas an earlier age of onset of 5 years or more was considered protective compared with WHO stage I 2. In Eswatini, HIV-positive children on ART and on antiretroviral drug regimen experienced viral suppression at a rate of 77.9%, with NVP-based ART having the lowest rates 3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of HIV-positive adolescents on antiretroviral therapy (ART) who were not virologically suppressed after 6 months was 23% in South Africa. WHO stage IV and ART-related facial outcomes were strongly associated with virological non-suppression, whereas an earlier age of onset of 5 years or more was considered protective compared with WHO stage I 2. In Eswatini, HIV-positive children on ART and on antiretroviral drug regimen experienced viral suppression at a rate of 77.9%, with NVP-based ART having the lowest rates 3.…”
Section: Introductionmentioning
confidence: 99%
“…WHO stage IV and ART-related facial outcomes were strongly associated with virological non-suppression, whereas an earlier age of onset of 5 years or more was considered protective compared with WHO stage I. 2 In Eswatini, HIV-positive children on ART and on antiretroviral drug regimen experienced viral suppression at a rate of 77.9%, with NVP-based ART having the lowest rates. 3 After 1–5 years on highly active ART (HAART), more than half of Nigerian children receiving HAART had a viral load above 1000 copies/mL.…”
Section: Introductionmentioning
confidence: 99%
“…Although the UNAIDS 95-95-95 strategy aims at ensuring that 95% of all people living with HIV (PLWH) are diagnosed, 95% of all PLWH diagnosed receive antiretroviral therapy (ART), and 95% of people on ART achieve sustained viral suppression, South Africa is still lagging behind in achieving these targets [ 1 – 4 ]. In KwaZulu-Natal (KZN), the province with the greatest burden of HIV in South Africa [ 5 , 6 ], there are HIV-hyperendemic areas where sustained viral suppression among PLWH is substantially lower (53.9%) than the UNAIDS target [ 7 ]. Studies have shown that population prevalence of detectable viraemia could infer the effectiveness of HIV treatment programmes as well as community HIV risk potential [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%